Comparison of early and late clinical outcomes in patients ≥80 versus <80 years of age after successful primary angioplasty for ST segment elevation myocardial infarction - TİGEN, MUSTAFA KÜRŞAT (Turkish Anaesthesiology and Intensive Care Society, 2013)
Objectives: We aimed to compare the efficacy of primary percutaneous coronary intervention (p-PCI) in patients ≥80 versus <80 years of age with ST-segment elevation myocardial infarction (STEMI). Study design: We retrospectively enrolled 2213 patients with acute STEMI. The patients were prospectively followed up for a median of 42 months. Early and late clinical outcomes were compared according to age. Results: One-hundred and seventy-nine (8.1%) of the 2213 patients were aged ≥80 years. Post-procedural TIMI grade 3 flow was significantly less frequent in the age ≥80 years patients (82.1% vs. 91.1%, p<0.001). Rates of mortality (14.5% vs. 3.4%, p<0.001), heart failure (20.7% vs. 10.5%, p<0.001), major hemorrhage (9.5% vs. 3.3%, p<0.001), secondary VT/VF (10.1% vs. 4.2%, p=0.002) and atrial fibrillation (12.8% vs. 4.3%, p<0.001) during the early hospitalization period were significantly higher in the age ≥80 years patient group. Overall rates of mortality (40% vs. 9.7%, p<0.001) and total stroke (5.6% vs. 1.1%, p=0.005) at long-term follow-up were also higher in the age ≥80 years patient group. However, there was no difference between the two groups with respect to the reinfarction/revascularization rates. Analysis, using the Cox proportional hazards model, revealed that age ≥80 to was an independent predictor of long-term mortality (hazard ratio 2.17, 95% CI 1.23-4.17, p=0.02). Conclusion: Age is an independent predictor of mortality after p-PCI for STEMI. Although it seems to improve early outcomes, the efficacy of p-PCI at long-term follow-up is limited in elderly patients. © 2013 Turkish Society of Cardiology.
Keywords: Age factors; Myocardial infarction/etiology/therapy; Percutaneous coronary intervention; Treatment outcome